Identification and expression of rpo19, a vaccinia virus gene encoding a 19-kilodalton DNA-dependent RNA polymerase subunit. - Ahn, B Y (1992)
The vaccinia virus DNA-dependent RNA polymerase subunit gene rpo19 was identified, and its expression was examined at RNA and protein levels. Antibody to the multisubunit RNA polymerase purified from virions reacted with a polypeptide with an apparent Mr of 21,000 that was synthesized in reticulocyte lysates programmed with (i) mRNA from infected cells that was isolated by hybridization to DNA subclones of the viral genomic HindIII A fragment and (ii) mRNA made in vitro by transcription of the viral open reading frame A6R. Polyclonal antiserum, raised to a recombinant protein product of the A6R open reading frame which could encode an 18,996-Da protein with an acidic N terminus, reacted with Mr-21,000 and -22,000 polypeptides that cosedimented with purified RNA polymerase. Internal sequencing of the two polypeptides confirmed that both were encoded by A6R, and the gene was named rpo19 to indicate the predicted molecular mass of the polypeptide in kilodaltons. Immunoblotting and metabolic labeling of infected cell proteins indicated that synthesis of the Mr-21,000 polypeptide started early and continued throughout virus infection, whereas the Mr-22,000 form appeared late following DNA replication. RNA analyses suggested that the rpo19 mRNA was expressed from a dual early/late promoter and that the protein-coding region of the mRNA was directly preceded by a short 5' poly(A) leader, apparently initiated within the TAAATG motif at the beginning of the open reading frame.